Tribological studies on polyetherketone composite under reciprocating sliding condition against steel cylinder - Harsha A.P.; Wäsche R.; Hartelt M. (My University, 2025)
Tribological studies on neat polyetherketone (PEK) and glass fiber reinforced PEK composite were carried out at room and elevated temperature (120'). The objective of this study was to characterize for friction and wear properties under dry reciprocating sliding condition at different experimental conditions. The polymer specimens were made to oscillate against steel cylinder as a counterpart. This kind of contact condition are frequently found in bushes, sliding bearing, electronic parts, seals, etc. The friction and wear behavior of neat PEK and composite was quite different at room temperature and elevated temperature. It was observed that glass fiber reinforcement is beneficial in controlling the wear of PEK matrix at room temperature than at elevated temperature. The test results are discussed by considering the surface properties i.e. material removal and film transfer formation. Scanning electron micrographs and optical micrographs of the worn polymer and steel cylinder was used to study the wear mechanisms. © IMechE 2015.